(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article studies the views of leading world scientists on the role of accelerators and incubators in financing innovative startups, analyzes the activities of accelerators and incubators in our country, and conducts a comparative analysis of the financing mechanisms used by accelerators and incubators in Uzbekistan and abroad, develops substantiated conclusions and proposals on the role of accelerators and incubators in financing innovative startups, and provides recommendations for their application in our country.